Low-dose RaDiation therapy for patients with KNee osteoArthritis (LoRD-KNeA): a protocol for a sham-controlled randomised trial - Jiyu Sun; Won Park; Dong Hyun Kim; Ji Hyun Lee; Joon Ho Wang; Hak Jae Kim; Kichul Shin; Min Jung Kim; Ji Young Kim; Byoung Hyuck Kim; Du Hyun Ro; Dae-Hee Lee; et al. (BMJ Open)
Introduction Low-dose radiation therapy (LDRT) for osteoarthritis (OA) has been performed for several decades. However, supporting evidence from randomised studies using modern methodologies is lacking, and a recently published randomised study failed to show the significant benefit of LDRT. The presented trial aims to evaluate the efficacy and safety of LDRT for patients with knee OA.Methods and analysis This prospective, multicentre, randomised trial will be conducted in the Republic of Korea. A total of 114 participants will be randomly assigned (1:1:1) to receive sham irradiation, 0.3 Gy/6 fractions of LDRT or 3 Gy/6 fractions of LDRT. Key inclusion criteria are primary knee OA with Kellgren-Lawrence grade 2–3 and visual analogue scale 50–90 when walking at the baseline. The primary endpoint is the rate of responders at 4 months after LDRT according to the OARSI-OMERACT criteria. Concomitant use of analgesics is prohibited until the primary efficacy evaluation is scheduled.Ethics and dissemination Currently, approval from the Ministry of Food and Drug Safety of the Republic of Korea and the institutional review board of each participating hospital has been obtained. Patient enrolment began in October 2022 and is ongoing at three participating sites. The results will be disseminated to academic audiences and the public via publication in an international peer-reviewed journal and presentation at conferences. This trial will provide valuable information on the safety and efficacy of LDRT for patients with knee OA.Trial registration number NCT05562271.